The Investigation of Work Safety: The Role of Training and Work Experience at a Flexible Packaging Company in Surabaya - Rahayu, Mutiara; Sawitri, Dewi Khrisna (Jurnal Economic Resource, 2025)
This study aims to analyze the role of training and work experience on the work safety of factory employees at flexible packaging company in Surabaya. The research background is based on the high rate of workplace accidents that still occur despite the company having conducted training programs and implemented safety policies. The research method employed is quantitative with an associative descriptive approach. The study involved a sample of 62 respondents obtained through purposive sampling. Data were analyzed using the Partial Least Squares (PLS) method with the assistance of SmartPLS software. The results indicate that both training and work experience have a significant effect on work safety. Training material and the level of knowledge acquired through work experience were found to be the most dominant indicators. These findings reinforce the importance of aligning training materials with the needs of each department and the necessity of empowering experienced employees in creating a safe work culture.